ACCESSORY SPLEEN IN GASTROSPLENIC LIGAMENT: A Case Report - Sofia jehanzeb; Bashir khan; Sumaria Noureen; Saad Salman; Saqib khan; Masood; Haseeb Shah (Journal of Bacha Khan Medical College, 2025)
Background: Bronchiectasis Accessory spleens are congenital anomalies resulting from incomplete fusion of splenic tissue during embryogenesis. They are usually asymptomatic and are often detected incidentally during imaging or surgical procedures. However, when located in atypical sites, they may pose diagnostic challenges. Case Presentation: We report the case of a 30-year-old male who presented to the emergency department with multiple abdominal stab wounds. Initial evaluation revealed mild hemoperitoneum on FAST scan. Emergency exploratory laparotomy was performed, which identified ileal perforation and mesenteric injury requiring surgical intervention. During the procedure, an incidental accessory spleen was discovered in the gastrosplenic ligament. Postoperative computed tomography confirmed the presence of an accessory spleen measuring approximately 12 × 11 × 11 mm. Conclusion: Accessory spleens, although usually clinically silent, should be considered in the differential diagnosis of intra-abdominal masses, particularly in atypical locations. Awareness of this anatomical variation is essential to avoid misdiagnosis and unnecessary surgical intervention.